Comparative efficacy of various oral hygiene care methods in preventing ventilator-associated pneumonia in critically ill patients: A systematic review and network meta-analysis. - Sachika Yamakita; Takeshi Unoki; Sachi Niiyama; Eri Natsuhori; Junpei Haruna; Tomoki Kuribara (PLoS ONE)
Oral hygiene care is important for ventilator-associated pneumonia prevention. However, the optimal oral hygiene care approach remains unclear. A network meta-analysis was conducted to compare the efficacy of various oral hygiene care methods for ventilator-associated pneumonia prevention in critically ill patients, and the methods were ranked. A literature search of three representative databases was conducted. We only analyzed parallel randomized controlled trials conducted to analyze the use antiseptics or toothbrushes in oral hygiene care for adult patients undergoing invasive mechanical ventilation in the intensive care unit. The outcome measure was the incidence of ventilator-associated pneumonia. Bias risk was assessed using the Cochrane Risk of Bias 2 tool, and the confidence in the evidence was evaluated using the CINeMA approach. Statistical analyses were performed using R 4.2.0., GeMTC package, and JAGS 4.3.1. The review protocol was registered in PROSPERO (registration number: CRD42022333270). Thirteen randomized controlled trials were included in the qualitative synthesis and twelve randomized controlled trials (2395 participants) were included in the network meta-analysis. Over 50% of the included studies were conducted in medical-surgical intensive care units. Ten treatments were analyzed and 12 pairwise comparisons were conducted in the 12 included studies. Analysis using surface under the cumulative ranking curves revealed that brushing combined with chlorhexidine 0.12% was most likely the optimal intervention for preventing ventilator-associated pneumonia (88.4%), followed by the use of chlorhexidine 0.12% alone (76.1%), and brushing alone (73.2%). Oral hygiene care methods that included brushing had high rankings. In conclusion, brushing combined with chlorhexidine 0.12% may be an effective intervention for preventing ventilator-associated pneumonia in critically ill patients. Furthermore, brushing may be the optimal oral hygiene care method for preventing ventilator-associated pneumonia in the intensive care unit. Further research is needed to verify these findings as the CINeMA confidence rate was low for each comparison.